THE IMPACT OF APPLYING BASE ISOLATOR IN HOSPITAL BUILDING - Predaricka Deastra; Jati Sunaryati; Riza Aryanti (Jurnal Rekayasa Sipil (JRS-Unand), 2014)
Due to Indonesia’s location in the earthquake zone, it is necessary for civil engineers in Indonesia to study seismic performance of a building, which is strongly related to the structure of the building itself. Buildings equipped with vibration damping structures, known as an isolation system, will have a different seismic behavior than if it did not have one. This is due to the impact of an earthquake dampening vibration isolator. This final project analyzes the difference between seismic performance of a building using a seismic isolation system and ones without. The conclusion of this final project shows that the isolation system will decrease the internal force of a structure element by about 57.71% for axial force, 84.10% for shear, and 85.75% for moment. The application of an isolation system will also decrease the relative displacement by about 74,28% and extended structure vibration period by about 171.17 %. Keywords: earthquake, seismic performance, isolation system.